Co-oligomers Based on 2-Methoxy, 5-(2’-ethylhexyloxy) phenylene and Thienylenevinylene for Organic Solar Cells - El Alamy, A.; Amine, A.; Bouzzine, Mohamed; Hamidi, M.; Bouachrine, M. (Orbital: The Electronic Journal of Chemistry, 2016)
Thanks to their optoelectronic properties and specific applications such as organic solar cells, the research on the lower band gap of organic p-conjugated materials encompassing both polymers and oligomers have been widely studied over the last years. The control of the band gap of these materials is a research issue of ongoing interest. In this study, theoretical study using the DFT method on four oligomers based on 2-methoxy, 5-(2’-ethylhexyloxy) phenylene and thienylenevinylene is reported. The theoretical ground-state geometry and electronic structure of the studied molecules were obtained by the DFT method at the B3LYP level with a 6–31G (d) basis set. Theoretical knowledge of the highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO) energy levels the gap energy (Eg) and the open-circuit voltage (Voc) of the studied compounds are calculated and discussed. The results of this work suggest these materials as a good candidate for organic solar cells.DOI: http://dx.doi.org/10.17807/orbital.v8i3.800